2009
DOI: 10.1158/1940-6207.capr-09-0169
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Delivery of Rapamycin Suppresses Tumorigenesis in a Mouse Model of Progressive Bladder Cancer

Abstract: Early-stage bladder cancer occurs as two distinct forms: namely, low-grade superficial disease and high-grade carcinoma in situ (CIS), which is the major precursor of muscleinvasive bladder cancer. Although the low-grade form is readily treatable, few, if any, effective treatments are currently available for preventing progression of nonmuscle-invasive CIS to invasive bladder cancer. Based on our previous findings that the mammalian target of Rapamycin (mTOR) signaling pathway is activated in muscle-invasive b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 17 publications
3
63
0
3
Order By: Relevance
“…Inhibition of mTOR signaling with rapamycin reduced cell proliferation and migration in vitro and reduced tumor volume in a T24-xenograft model by 55%. 71 These results were supported by a second study that showed mTOR activation in muscle-invasive UCC, 1,72 with mTOR inhibition preventing the progression of CIS to invasive bladder cancer. 72 Another important role of mTOR in tumor biology is the induction of angiogenesis.…”
Section: Role Of Mtor In Bladder Cancermentioning
confidence: 82%
See 1 more Smart Citation
“…Inhibition of mTOR signaling with rapamycin reduced cell proliferation and migration in vitro and reduced tumor volume in a T24-xenograft model by 55%. 71 These results were supported by a second study that showed mTOR activation in muscle-invasive UCC, 1,72 with mTOR inhibition preventing the progression of CIS to invasive bladder cancer. 72 Another important role of mTOR in tumor biology is the induction of angiogenesis.…”
Section: Role Of Mtor In Bladder Cancermentioning
confidence: 82%
“…71 These results were supported by a second study that showed mTOR activation in muscle-invasive UCC, 1,72 with mTOR inhibition preventing the progression of CIS to invasive bladder cancer. 72 Another important role of mTOR in tumor biology is the induction of angiogenesis. mTOR regulates the expression of hypoxia inducible factor and thus subsequently of vascular endothelial growth factor (VEGF).…”
Section: Role Of Mtor In Bladder Cancermentioning
confidence: 82%
“…In bladder cancer cell lines, mTOR inhibition with rapamycin has been shown to significantly decrease bladder cancer cell proliferation and induce G 0 /G 1 cell-cycle arrest without stimulating apoptosis in vitro and in vivo. [24][25][26] In our panel of cell lines, rapamycin induced heterogeneous and partial growth arrest that plateaued at drug concentrations around 10 nM (Fig. 6).…”
Section: Resultsmentioning
confidence: 81%
“…10). Therefore, and as reported in this issue of the journal, the Abate-Shen group (Seager et al) evaluated local versus systemic delivery of rapamycin, an inhibitor of the TOR complex 1/mTOR complex, for effects on the progression of CIS lesions in their mouse model (11). Their results indicate that mTOR inhibition produces striking inhibitory effects on tumor progression.…”
mentioning
confidence: 99%